Pengaruh Kepuasan Kerja, Lingkungan Kerja dan Work Life Balance Terhadap Loyalitas Karyawan pada KSP CU Mandiri Kota Tebing Tinggi - Dela Januario Hilarius Situmorang; Aidil Hadi; Eka Mayastika Sinaga; Mhd. Sofian (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the Influence of Job Satisfaction, Work Environment and Work Life Balance on Employee Loyalty at KSP CU Mandiri Tebing Tinggi City. The research method used is a quantitative method using the SPSS version 25.00 program. The sample of this study was 33 respondents, namely office employees at KSP CU Mandiri Tebing Tinggi City. Data collection techniques used interview and questionnaire techniques. Data analysis techniques used in this study used instrument tests such as validity and reliability tests, then classical assumption tests such as normality tests, multicollinearity tests, heteroscedasticity tests. Furthermore, multiple linear regression analysis tests, coefficient of determination (R2) and hypothesis tests. The results of the study indicate that job satisfaction affects employee loyalty at KSP CU Mandiri Tebing Tinggi City. The work environment affects employee loyalty at KSP CU Mandiri Tebing Tinggi City. Wok life balance affects employee loyalty at KSP CU Mandiri Tebing Tinggi City. Then job satisfaction, work environment and wok life balance simultaneously affect employee loyalty at KSP CU Mandiri Tebing Tinggi City.